2019
DOI: 10.4314/sajas.v49i4.12
|View full text |Cite
|
Sign up to set email alerts
|

Lactation performance and blood metabolites in lactating dairy cows micro-supplemented with <i>Moringa oleifera</i> leaf meal

Abstract: This study examined the effects of micro-supplementation of Moringa oleifera leaf meal on lactation performance and blood metabolites of lactating dairy cows. Thirty Jersey cows (± 40 days in milk (DIM)) were supplemented with Moringa oleifera leaf meal (M) at 0 (M0), 30 (M30) and 60 g/cow/day. The experiment lasted until 90 DIM with 14 days adaptation. Milk yield was recorded daily and samples were collected once weekly to determine milk composition and total antioxidant capacity (MTAC). Blood samples were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 32 publications
7
10
0
Order By: Relevance
“…All estimated values of blood parameters in this study were within the normal reference ranges ( Boyd, 2011 ). The significant increase in serum glucose accompanied by a significant decrease in serum cholesterol was consistent with other studies ( Kholif et al, 2016 , Kholif et al, 2018 , Kekana et al, 2019 ). Dietary inclusion of M. oleifera significantly decreased the concentrations of serum triglycerides and cholesterol but increased (p < 0.05) the concertation of serum glucose in lactating goats ( Kholif et al, 2016 ) and lactating dairy cows ( Zeng et al, 2018 ).…”
Section: Discussionsupporting
confidence: 92%
“…All estimated values of blood parameters in this study were within the normal reference ranges ( Boyd, 2011 ). The significant increase in serum glucose accompanied by a significant decrease in serum cholesterol was consistent with other studies ( Kholif et al, 2016 , Kholif et al, 2018 , Kekana et al, 2019 ). Dietary inclusion of M. oleifera significantly decreased the concentrations of serum triglycerides and cholesterol but increased (p < 0.05) the concertation of serum glucose in lactating goats ( Kholif et al, 2016 ) and lactating dairy cows ( Zeng et al, 2018 ).…”
Section: Discussionsupporting
confidence: 92%
“…The provision of MOLP met the energy requirements more efficiently in early pregnancy by improving the plasma sugar contents. Our findings were in line with the results of a previous study on Jersey cows (63). In addition, MOLP supplementation also improved the bioavailability of carotenoids and lycopene to ameliorate metabolic and hematological perturbations by reducing LPO and inflammatory cytokines (64).…”
Section: Discussionsupporting
confidence: 92%
“…Also, a study carried out by Adegun and Aye [ 41 ] in West African Dwarf Rams sheep reported that supplementation of Pannicum maximum with MO meal had no effect on the IBW, FBW and BWC, but DMI decreased as MO supplementation levels increased. On the other hand, Kekana et al [ 14 ] microsupplemented Jersey cows with 0, 30 and 60 g of MO meal per animal per day and did not observe differences in DMI and BWC. In the present study, the animals’ basal diets allowed them to meet their nutritional requirements, which was reflected in a positive performance throughout the experiment.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that dietary inclusion of MO in Najdi ewes improved milk yield and milk quality. On the other hand, [ 14 ] supplemented Jersey cows with 30 and 60 g of MO meal per animal per day exhibited no differences in DMY, protein or lactose, but fat increased at a dose of 60 g d −1 compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation